The Political Development; An attempt to determine –the concept knowledge dimensions and indicators - Assistant professor, Dr.Nadhim Nawaf Ibrahim (Tikrit Journal For Political Science, 2024)
The development of political act is one of the comprehensive development act . studying the political development primarily deals with the elements of political of political system, its public institution, and their actions this also is connect with the necessity of develop meant the systematic political structure, and finding specialized institutions process, in addition, the process of political development always combined with tensions and divisions in other words crisis that have different effects ,so treating this problems need time but leads the society finally to establish modern democratic system.